Estrategias de marketing para el local "Doctor Glass" ubicado en la calle García Moreno, en la ciudad de Babahoyo, periodo 2022. - Dumani Campos, Leonardo Isaac (2023)
This case study called “Marketing strategies for the "Doctor Glass" store located on García Moreno Street, in the city of Babahoyo, period 2022, is structured in the line of research Financial, administrative, tax, audit and control management, and focused on the Marketing and Advertising subline. The objectives of this case study are to evaluate the strategies that the company has been applying, as well as to determine the various strategies that exist, to analyze the impact they may have on the company and thus be able to classify and prioritize the goal that is expected to be obtained. apply them. Regarding the conceptualization of the work, information was collected about the different types of marketing strategies that exist and that are in accordance with the economic activity of the company and can be favorable for its growth and achievement of its objectives. This work has applied the observational research methodology, focused on the preferences and opinions of users, in order to obtain important information that can be of benefit to the company. The qualitative and quantitative method was also applied through an interview. directed. to the owner and a survey answered by customers